Análisis comparativo del presupuesto asignado para la salud en Colombia durante los años 2020 y 2021 (2022)
For a correct economic and social development of our nation, it is necessary to plan the annual budget properly, just as it is done in any company. For this reason, a budget allocation should be made with the aim of meeting the needs of; debt, investment, social and economic development, as well as planning own income or debt. And since in the year 2020 the World Pandemic by Covid-19 was presented; it became necessary to define more priorities in health issues. The main objective of this article is to show the items allocated in Colombia for the health category during the 2020 and 2021 periods, and to determine if the National budget was affected or decreased, due to the way in which these resources were allocated, in addition to This concretely presents the regulations that regulate the planning and allocation of resources in Colombia, as well as the regulations approved for the 2020 and 2021 periods and their budget breakdown for the health sector. Through the reading of the present it can be evidenced that the national government gave special importance to the protection of the population, and the Ministry of health and protection did everything possible to adjust to the assignments given by law.